Students’ Perceptions of Islamic Religious Education about Islam and Radicalism: A Study of Three PTKIN Central Java - Rochanah, Rochanah (Bulletin of Science Education, 2021)
It is hard to argue that religion has a role in triggering the occurrence of violence that occurs between religious communities. The mistake of Muslims in understanding religion has resulted in Islam showing a radical face. The negative label probably needs to be re-aligned so that the image of Islam returns to its good nature according to its essence. In this case, students as intellectuals have a big role in straightening it out. The aim of this study analyse the students’ perceptions of islamic religious education about islam and radicalism: a study of three PTKIN central Java. This research is a field research with a descriptive analytical qualitative approach. Data collection techniques were carried out through observation, interviews and documentation. The results showed that the current situation of Muslims has not been able to properly practice their religious teachings so that what is practiced in their daily lives does not run in harmony with what is contained in the Qur'an. This is the initial cause of the emergence of acts of violence in the name of religion. In reality, radicalism is shown in dishumanist actions that appear in several tragedies framed in the name of religion. This raises the perception that Islam is a radical religion. However, Muslims must prove that the negative label directed at Islam is a very baseless argument because Islam is not a terrorist religion and all actions that lead to acts of terror are not essentially Islamic teachings. Keywords: Students’ Perceptions, Radicalism, Islamic Religious Education